2021
DOI: 10.1302/2633-1462.27.bjo-2021-0044.r1
|View full text |Cite
|
Sign up to set email alerts
|

The orthopaedic waiting list crisis

Abstract: Aims Due to widespread cancellations in elective orthopaedic procedures, the number of patients on waiting list for surgery is rising. We aim to determine and quantify if disparities exist between inpatient and day-case orthopaedic waiting list numbers; we also aim to determine if there is a ‘hidden burden’ that already exists due to reductions in elective secondary care referrals. Methods Retrospective data were collected between 1 April 2020 and 31 December 2020 and compared with the same nine-month period t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 17 publications
(17 reference statements)
1
17
0
Order By: Relevance
“…Blood loss is a key surgical morbidity, and reduced duration of surgery impacts provision of both orthopaedic and anaesthetic services, especially given widespread increased systemic pressures around the COVID-19 pandemic, the additional morbidity associated with prolonged anaesthesia, and environmental concerns surrounding inhaled anaesthetics. [54][55][56][57] Three studies reported on mechanical alignment, which may be predictive of impaired long-term functionality and subsequent development of osteoarthritis, at follow-up, and concluded there was no difference in alignment between synthetic and autologous bone grafts. 32,33,35,47,58 Functional outcome data in our evidence base was limited and showed no preference for synthetic or autologous bone grafts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood loss is a key surgical morbidity, and reduced duration of surgery impacts provision of both orthopaedic and anaesthetic services, especially given widespread increased systemic pressures around the COVID-19 pandemic, the additional morbidity associated with prolonged anaesthesia, and environmental concerns surrounding inhaled anaesthetics. [54][55][56][57] Three studies reported on mechanical alignment, which may be predictive of impaired long-term functionality and subsequent development of osteoarthritis, at follow-up, and concluded there was no difference in alignment between synthetic and autologous bone grafts. 32,33,35,47,58 Functional outcome data in our evidence base was limited and showed no preference for synthetic or autologous bone grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Blood loss is a key surgical morbidity, and reduced duration of surgery impacts provision of both orthopaedic and anaesthetic services, especially given widespread increased systemic pressures around the COVID-19 pandemic, the additional morbidity associated with prolonged anaesthesia, and environmental concerns surrounding inhaled anaesthetics. 54 - 57 …”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic of our age, elective surgeries have been ceased in most countries to reduce hospital admissions and to direct facilities to pandemic patients (6,8,9,(12)(13)(14). In orthopedics, especially patients who are waiting for knee and hip arthroplasties are affected by this situation, and they are forced to live with a very low quality of life, which is described as "worse than death" situation in the literature (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…A significant drop in the elective surgical output across specialities was observed during the year 2020 due to resources being diverted to tackling the coronavirus disease 2019 (COVID-19) crisis [ 1 ]. This has led to a significant number of patients being forced to wait an inordinate amount of time to receive elective treatments in trauma and orthopaedic surgery.…”
Section: Introductionmentioning
confidence: 99%